Análise proteômica comparativa de linhagens celulares de melanoma e melanócito murinos frente ao tratamento com fração proteolítica derivada do látex de Vasconcellea cundinamarcensis - Fernanda de Oliveira Lemos (2014)
Previous studies showed that CMS-2 proteolytic fraction, obtained from the Vasconcellea cundinamarcensis latex, significantly reduced the number of metastasis in animals bearing colon carcinoma and melanoma, and in vitro, increased DNA fragmentation and decreased adhesion and cell invasion. Here, we present a proteomic analysis of cell lysates from metastatic melanoma B16-F10 and melanocyte Melan-a, both murine, treated with CMS-2 (10 μg/mL, 24 h), in order to identify modulated proteins related to tumor and/or metastatic development. Using the techniques of two-dimensional electrophoresis DIGE and mass spectrometry, it was possible to identify 71 spots differently expressed between controls - Melan-a (MC) and B16-F10 (BC). When MC and BC are compared to their respectives treated groups, Melan-a (MT) and B16-F10 (BT), selective effects, on B16-F10, were observed in 21 spots expression levels. CMS-2 statistically reduced the expression of 4 proteins (nucleophosmin 1, heat shock protein 65, calcyclin binding protein and eukaryotic translation initiation factor 4H), overexpressed in BC, to similar levels of MC. These proteins are related to the proliferation, survival, migration and cell invasion. The antioxidant and glycolytic enzymes superexpression, after exposure to CMS-2, was observed and may be related to the oxidative phosphorylation reduction, as determined by the resazurin metabolism, and melanogenesis induction (differentiation marker), measured by content of melanin and tyrosinase activity. The decreased expression of actin- β and γ and cofilin 1, proteins involved in cell motility, may explain the reduction of B16-F10 and Melan-a cell migration observed after CMS-2 treatment. The reduction, even partially, of cyclophilin A, protein disulfide isomerase A3 precursor and calreticulin precursor, chaperones superexpressed in tumor cells, and guanosine diphosphate (GDP) dissociation inhibitor 2, which at high levels promote epithelial mesenchymal transition and prevents the activation of caspases, may also justify the cellular effects observed in the presence of CMS-2. In conclusion, CMS-2 can reverse the protein expression, in B16-F10 cells, related to tumor progression and metastasis to normal melanocytic line patterns. This effect justifies the CMS-2 antimetastatic activity and supports in clarifying the mechanism(s) of action.